THE IMPACTS OF PHYSICAL ACTIVITY ON MENTAL HEALTH IN PATIENTS WITH BURNOUT SYNDROME: A SYSTEMATIC REVIEW (CIPEEX, 2025)
Through a systematic review of the scientific literature, we analyze that physical activity has a notable influence on Burnout Syndrome, improving the individual's well-being and promoting health and a better quality of life. Four articles available in the PubMed and SciELO databases were analyzed, using instruments such as the Maslach Burnout Inventory and the SF-36. The objective of the study was to capture the impacts of physical activity on mental health in patients affected by Burnout Syndrome. The results of the review point to a positive association between physical exercise and improved quality of life and health perception in these individuals.
Keywords: Burnout Syndrome; Physical Activity; Mental Health